Case reports of hydatid disease - Usharani, A. (J Epidemiol Glob Health, 2013)
Two cases of hydatid cyst were reported in the Microbiology department, Siddartha Medical College in 2011. 42 year old female presented with a history of painless swelling in the right inguinal region for 5 years which was insidious in onset and gradually increasing in size. She developed itching prior to the hospital visit. 40 year old male presented with abdominal swelling since 1 year, not associated with vomiting or jaundice. Both the patients were from rural background. Conclusion. Echinococcus granulosus can cause cystic lesions anywhere in the body. High degree of suspicion of hydatid disease is essential in endemic areas in cystic lesions.